Правова природа інтерпретаційних актів Конституційного Суду України - Шевчук, Ірина Миколаївна; Shevchuk, Iryna M. (Запорізький національний університет, 2012)
У статті наведені результати наукового аналізу правової природи інтерпретаційних актів Конституційного Суду України. Автором досліджено особливості інтерпретаційних актів Конституційного Суду України.This article deals with the results of scientific analysis of the legal nature of interpretative acts of the Constitutional Court of Ukraine. The peculiarities of interpretative acts of the Constitutional Court of Ukraine are investigated. It is defined that interpretative acts of the Constitutional Court of Ukraine occupy a particular place in the system of legal acts, as they share the characteristics of both interpretative and normative acts. When interpreting the Constitution and the laws of Ukraine they reveal their true content and form a single constitutional understanding of the law. It is indicated that normative nature of a legal act does not mean that it belongs to normative legal acts. Interpretative acts belong to the acts of normative character, as they contain norms of interpretation, but not new legal rules. It is determined that the legal force of interpretative acts comes out of the legal status of the Constitutional Court of Ukraine and reveals its peculiarities. Interpretative acts, which are adopted by the Constitutional Court of Ukraine are obligatory to be fulfilled on the territory of Ukraine, they are final and cannot be appealed, non-fulfilment of the decisions leads to the responsibility before the law. The accent is put on the fact that none of the laws presupposes a norm about the responsibility for non-fulfilment of the decisions of the Constitutional Court of Ukraine. The functioning of the interpretative legal acts in time, space and as to the scope of persons is viewed. The author concludes that the acts function during the validity period of the legal norm they interpret. Though, the functioning of the interpretative legal acts depends on the following conditions: if the normative legal act is cancelled, consequently the act of its official interpretation loses its force; if a new normative legal act contains norms similar to those contained in the previous act, the principles of the interpretative act dealing with these norms preserve their force; if in a new normative legal act the norm was changed or completed but preserves the terms and principles used in the previous edition, the explanations of the principles and terms in the act of official interpretation which are present in a new edition, preserve their force. It is determined that the functioning of the interpretative legal acts is extended to the territory, defined in the powers given to the subject with the purpose to officially interpret legal norms. Interpretative acts are obligatory for persons that are under the jurisdiction force of the subject that issued that act. Interpretative acts of the Constitutional Court of Ukraine, which cancel or lessen the person’s responsibility, have retroactive effect in time.
Legal nature of the interpretative acts of the Constitutional Court of Ukraine
Keywords: акти Конституційного Суду України; інтерпретаційно-правовий акт; офіційне тлумачення; нормативність; acts of the Constitutional Court of Ukraine; interpretative legal act; official interpretation; normativity